Effect Of Sodium Dodecyl Sulfate On Viscometric Properties Of Methanol, Ethanol, n-Propanol And iso-Propanol At Different Temperatures (Journal of the Bangladesh Chemical Society, 2013)
The critical micelle concentration (CMC) of Sodium Dodecyl Sulfate (SDS) in water was determined from the conductance and viscosity measurement. The estimated value of CMC was found to be 0.0085 mol.L-1 at 29°C. The concentration of SDS in pre-micellar and post-micellar region of 0.005M and 0.01M, respectively were used for the viscometric measurements of Methanol, Ethanol, n-Propanol, iso-Propanol at different temperatures. Viscosities of ternary mixtures of Methanol, Ethanol, n- Propanol and iso-Propanol in 0.005M and 0.01M aqueous SDS have been studied over the entire range of composition at 298.15- 323.15K with an interval of 5K except Methanol. Methanol system was studied at 298.15-308.15K owing to its low boiling point. Viscosities increase rapidly with alcohol concentration and show maxima in aqueous SDS rich region at 0.2 0.3 mole fraction of alcohols. The position of maxima virtually does not change remarkably with the variation of temperature. The excess viscosities, ?E values are found to be positive and large in magnitude, indicating that aqueous SDS solutions of alcohols are highly non ideal. The heights of the maxima are in the order:iso-Propanol + aqueous SDS > n-Propanol + aqueous SDS > Ethanol + aqueous SDS > Methanol + aqueous SDS.The excess viscosities, ?E data have been fitted by the least square method to the four parameter Redlich-Kister equation and the values of the parameter aj have been reported. Journal of Bangladesh Chemical Society, Vol. 25(2), 110-123, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15046